2022
DOI: 10.3390/coatings12091279
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Coatings’ Role in Transparency, Mechanical Hardness, and Wetting Angle Increase

Abstract: Among the different nanostructures involved in the improvement of material properties, carbon nanotubes occupy a specific place because of their small refractive index, extended surface, and large Young’s module, which can all provoke dramatic change in basic matrix material characteristics. Inorganic crystals, semiconductors, metals, conductive compounds, and some polymer structures whose surfaces are treated with carbon nanotubes demonstrate better features than the ones obtained before carbon nanotubes depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Carbon materials, including carbon nanotubes and graphene nanosheets, have been used as reinforcements in Mg-based composites due to their unique structure and very high Young's modulus [21,63,64]. Due to the small diameter and very high mechanical hardness of CNTs, if they are densely placed on the surface of the medical instrument, the obtained lotus effect can provide protection against corrosion as well as bacteria and viruses [65,66]. Abazari et al [27] showed that the continuous distribution of graphene oxide (GO) reinforcement has a positive effect on the microstructure, mechanical properties, and corrosion resistance of the Mg matrix, while the O-containing groups in GO also promote the deposition of the corrosion product layer [27].…”
Section: Mg/mgo Np Compositesmentioning
confidence: 99%
“…Carbon materials, including carbon nanotubes and graphene nanosheets, have been used as reinforcements in Mg-based composites due to their unique structure and very high Young's modulus [21,63,64]. Due to the small diameter and very high mechanical hardness of CNTs, if they are densely placed on the surface of the medical instrument, the obtained lotus effect can provide protection against corrosion as well as bacteria and viruses [65,66]. Abazari et al [27] showed that the continuous distribution of graphene oxide (GO) reinforcement has a positive effect on the microstructure, mechanical properties, and corrosion resistance of the Mg matrix, while the O-containing groups in GO also promote the deposition of the corrosion product layer [27].…”
Section: Mg/mgo Np Compositesmentioning
confidence: 99%
“…The principal difference separating the LOD technique from other methods is the ability to deposit CNTs on materials with various natural structures (metals [40], ceramics [41,42], and semiconductors [23]) via their implantation under the influence of an electrical field [43]. The feature of CNT implantation controlled under an external electric field allows for finding the optimal deposition regime with a significant improvement of the mechanical and optical properties [23,[40][41][42][43][44]. It should be mentioned that for the system "ITO-CNTs", a dramatic change in wettability is observed.…”
Section: Introductionmentioning
confidence: 99%